Some activities for the development and innovation of small and medium-sized enterprises on the example of Рoland - Rejman, K. (Економічні інновації, 2014)
The article presents some of the activities undertaken for the development of small and medium-sized enterprises in Poland with particular emphasis on the development of innovation in these enterprises. It also presents some barriers existing in the processes aimed at increase the innovativeness of Polish enterprises in the above mentioned sector.